SCF(β-TRCP) links Chk1 signaling to degradation of the Cdc25A protein phosphatase - Jin, Jianping (Cold Spring Harbor Laboratory Press, 2003)
Eukaryotic cells respond to DNA damage and stalled replication forks by activating protein kinase-mediated signaling pathways that promote cell cycle arrest and DNA repair. A central target of the cell cycle arrest program is the Cdc25A protein phosphatase. Cdc25A is required for S-phase entry and dephosphorylates tyrosine-15 phosphorylated Cdk1 (Cdc2) and Cdk2, positive regulators of cell division. Cdc25A is unstable during S-phase and is degraded through the ubiquitin-proteasome pathway, but its turnover is enhanced in response to DNA damage. Although basal and DNA-damage-induced turnover depends on the ATM-Chk2 and ATR-Chk1 pathways, how these kinases engage the ubiquitin ligase machinery is unknown. Here, we demonstrate a requirement for SCF(β-TRCP) in Cdc25A turnover during an unperturbed cell cycle and in response to DNA damage. Depletion of β-TRCP stabilizes Cdc25A, leading to hyperactive Cdk2 activity. SCF(β-TRCP) promotes Chk1-dependent Cdc25A ubiquitination in vitro, and this involves serine 76, a known Chk1 phosphorylation site. However, recognition of Cdc25A by β-TRCP occurs via a noncanonical phosphodegron in Cdc25A containing phosphoserine 79 and phosphoserine 82, sites that are not targeted by Chk1. These data indicate that Cdc25A turnover is more complex than previously appreciated and suggest roles for an additional kinase(s) in Chk1-dependent Cdc25A turnover.